Isolation and Selection of Potentially Beneficial Autochthonous Bacteria for Piaractus mesopotamicus Aquaculture Activities - Guidoli, Marcos Gabriel (2015)
Piaractus mesopotamicus is the most produced specie in Argentinian fish culture with an annual production of 2,017 tons. Thehigh demands of specimens generated a deficit of larvae, juveniles and sexually mature adults. The high stress conditions and theincidence of diseases had intensified this deficit. Probiotics are proven to increase survival and growth rates in aquaculture. Thefirst step in the design of a putative probiotic is the selection of adequate microorganisms to boost fish health. Lactic Acid Bacteriaand Bacillus are generally accepted as probiotics in aquaculture. In this work we obtained 522 isolates from different anatomicalparts of P. mesopotamicus, with a total of 30 lactic acid bacteria (LAB) and 8 Bacillus strains submitted for the evaluation of theirbeneficial properties. Only eight of these strains were selected for further "in vivo" assays based on following criteria: production ofinhibitory metabolites and biosurfactants, screening of antagonistic activity against foodborne and pathogenic microorganisms, abilityto emulsify polar solvents and compatibility between strains. All selected microorganisms were identified by sequencing 16S RNAgene. Pure cultures of all strains herein studied are preserved in Centro de Referencia de Lactobacilos (CERELA-CONICET) andLaboratorio de Sanidad Animal of the Estación Experimental Agropecuaria Rafaela, Instituto Nacional de Tecnología Agropecuaria(INTA) culture collections